Evaluation of performance characteristics of Jatropha Biodiesel blend in a single-cylinder Diesel Engine: A simulation approach - Ghimire, Bhuwan; Gautam, Oscar; Karn, Rupesh Lal; KC, Aparajita; Sharma, Bibek; Adhikari, Surya Prasad (Journal of Innovations in Engineering Education, 2025)
This study evaluates the performance characteristics of Jatropha biodiesel blends using Ricardo Waive software. A simulation model of a 3.5 kW variable compression ratio diesel engine was developed with all possible geometric parameters. The test was conducted by varying the load from 0.5 kg to 12 kg. Jatropha biodiesel blends were prepared based on Fatty Acid Methyl Ester (FAME) data, including 10JBME (10% Jatropha biodiesel, 90% diesel), 15JBME (15% Jatropha biodiesel, 85% diesel), and 20JBME (20% Jatropha biodiesel, 80% diesel). Performance parameters such as indicated power (IP), brake-specific fuel consumption (BSFC), mechanical efficiency (ME), brake thermal efficiency (BTE), and exhaust gas temperature (EGT) were analyzed. The results showed that deviations in performance characteristics between biodiesel blends and pure diesel were within 5%. Lower blends (e.g., 5JBME) exhibited better IP, ME, and BTE, while higher blends (e.g., 10JBME and 20JBME) improved EGT. These findings indicate that moderate blends strike a balance between fuel efficiency and power output, whereas higher blends may reduce efficiency due to the lower energy content of biodiesel. A 20% Jatropha biodiesel and 80% diesel blend is considered moderate, balancing fuel efficiency and power output.